EFFECT OF SERVICE QUALITY AND BRAND TRUST ON CUSTOMER SATISFACTION AND CUSTOMER LOYALTY PERTAMINA HOSPITAL BALIKPAPAN - Lenny Meitha Wulur; Theresia Militina; Gusti Norlitaria Achmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This research was conducted by Lenny titled